Not just helping: What and how older men learn when they volunteer. Issue 3 (3rd March 2016) - Chen, Li-Kuang
ABSTRACT: Participation or active engagement with life is advocated internationally and is the core for successful aging of individuals. Although participating in volunteering has been proven to benefit older adults' health and well-being, men participate less in volunteerism than do women. Experiences are considered the primary resources for adults' growth and learning, yet learning when helping others has been rarely explored. This study provides a new perspective by exploring volunteering as a resource for learning. The purpose of the study was to understand the learning process when older men help others. A total of 17 men aged 60 years and above who had volunteered regularly for at least 2 years were interviewed. Findings, reached by inductive analysis, indicated that these men perceived the learning during volunteering differently from classroom learning. Although learning had not been their intention or focus, the men did develop, in multiple ways, knowledge, skills, and wisdom through volunteering. We concluded that volunteering provides a holistic context with the three attributes of learning: (a) using experience as a foundation; (b) building content that is practical, wide, and diverse; and (c) employing multiple methods and flexibility. Building upon plentiful life experiences, volunteering is a learning context as well as a learning resource for older men, which makes successful aging a reachable aim.